Comparison of integrated versus parallel continuous renal replacement therapy combined with veno-venous extracorporeal membrane oxygenation in patients with COVID-19 ARDS - Kristina Schönfelder; Felix Helmenstein; Frank Herbstreit; Johanna Reinold; Andreas Kribben; Michael Jahn; Justa Friebus-Kardash (BMC Anesthesiology)
Abstract Introduction Acute kidney injury (AKI) is a common complication of acute respiratory distress syndrome (ARDS) and multiple organ dysfunction syndrome (MODS) in patients receiving extracorporeal membrane oxygenation (ECMO) support, leading to requirement of continuous renal replacement therapy (CRRT) in 70% of ECMO patients. Parallel arrangement of CRRT and ECMO circuits is common in adult patients. However, CRRT may also be integrated directly into the ECMO circuit. This study compares the safety of both approaches. Methods This retrospective analysis included 105 patients treated with continuous veno-venous haemodiafiltration and veno-venous ECMO (Cardiohelp©) for COVID-19-induced ARDS between April 2020 and December 2021. Of these, 48 patients received a parallel connected CRRT running independently from ECMO (parallel approach), while in 57 patients, CRRT was integrated into the ECMO circuit (integrated approach) by connecting the CRRT access line to the post-oxygenator port and the CRRT return line to the pre-oxygenator position. Local protocol for risk assessment of this device combination mandated a maximum return line pressure below 250 mmHg in the CRRT system. Results At CRRT initiation, the integrated group had significantly higher median pressures in CRRT lines compared to the parallel approach group (access line 110 mmHg vs. -25 mmHg, return line 170 mmHg vs. 50 mmHg; p < 0.01). However, median transmembrane pressures were similar between both groups (20 mmHg vs. 20 mmHg, p = 0.16). In-hospital mortality (p = 0.99), catheter associated infections (p = 0.47), bacteraemia (p = 0.96), filter clotting (p = 0.58) and unplanned CRRT system changes (p = 0.45) within the first 72 h of CRRT were comparable between both groups. The integrated group exhibited higher rates of bleeding events (37% vs. 23%; p = 0.08). Thromboembolism occurred in four cases in the integrated group, while one pneumothorax was observed in the parallel group. No cases of air embolism, device associated haemolysis or blood leakage was documented. Conclusions Despite higher pressures in CRRT lines, the integrated approach provided comparable safety to the parallel approach. In case of hygienically challenging settings (such as the COVID-19 pandemic), the minimization of extracorporeal accesses and the streamlining of alarm management are decisive factors in providing intensive care medicine. Therefore, the integrated configuration of CRRT into the ECMO circuit can be advantageous in daily intensive care medicine.